Location Quotient and Shift Share Analysis for Sragen’s Economic Potential - Naufal Azaki (University of Merdeka Malang, 2024)
This study employs the basic economic theory approach to evaluate the performance of regional economic development in Sragen Regency, Central Java Province. The primary objective is to identify the base/leading and prospective economic sectors that could bolster regional productivity. The study utilizes a quantitative approach, employing the Location Quotient and Shift Share methods. The data used for this analysis is the secondary data of the Gross Regional Domestic Product (GRDP) of Sragen Regency and Central Java Province from 2015 to 2019. The research findings reveal six sectors as the base/leading and prospective sectors. These include Agriculture, Forestry and Fisheries, Electricity and Gas Procurement, Wholesale and Retail Trade, Car and Motorcycle Repair, Corporate Services, and Other Services. These sectors are considered pivotal in driving the region’s economic growth. In addition to these, ten other sectors, while not being the base, show prospective development. These sectors present potential opportunities for further economic expansion. However, the Mining and Quarrying sector falls into the category of non-basis and is not considered a prospective sector. The Shift Share Analysis results indicate that the Manufacturing Industry outperforms other sectors in terms of competitiveness in the Sragen Regency. This suggests that the Manufacturing Industry holds a significant position in the region’s economic landscape. In conclusion, the study provides valuable insights into the economic sectors that are instrumental in strengthening regional productivity in Sragen Regency. It also highlights the sectors with potential for future development, thereby guiding strategic planning for regional economic growth.